1989
DOI: 10.1111/j.1095-8649.1989.tb03026.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt intake and its relevance to ionic regulation in freshwater salmonids

Abstract: Dietary sodium intake for freshwater salmonids feeding in the wild (invertebrate diet) or in captivity (pellet diet) was calculated and compared with published branchial sodium influx values. Dietary sodium intake (mmol kg-' per month) increases from winter minimum values of 5 and 3C-40 to reach maximum values in summer of 175 and 240 for invertebrate and pellet diet, respectively. In summer, dietary sodium intake for fish feeding in the wild was of the same magnitude as branchial sodium influx. The implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 9 publications
1
38
0
1
Order By: Relevance
“…Previous studies have shown that a dietary source of Na + can be just as important as a waterborne source for meeting physiological requirements in rainbow trout (Smith et al, 1989(Smith et al, , 1995. Almost 100% of the Na + taken up from the diet is absorbed though the gut and taken up into the plasma (Smith et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that a dietary source of Na + can be just as important as a waterborne source for meeting physiological requirements in rainbow trout (Smith et al, 1989(Smith et al, , 1995. Almost 100% of the Na + taken up from the diet is absorbed though the gut and taken up into the plasma (Smith et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 100% of the Na + taken up from the diet is absorbed though the gut and taken up into the plasma (Smith et al, 1995). Fish can lose Na + through their gills, liver (via biliary excretion) and kidneys, although Na + loss through the gills is much more important than other routes (Smith et al, 1989). Fish maintain Na + homeostasis by modulating influx and efflux, primarily at the gills, as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In freshwater salmonids, NaCl uptake from food may potentially exceed uptake from the water across the gills (Smith et al, 1989), a fact that was often overlooked until recently (reviewed by Wood and Bucking, 2011). Under the Amazonian soft water conditions, food might be an important source of ions, especially when the energy available for branchial uptake processes is limited under severe hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, parental mucus may act as a direct source of ions. Freshwater fish replace ions lost by passive efflux to the external environment through the active uptake of ions across the gills or through the diet (Smith et al, 1989). Experimental diets rich in ions help satisfy the osmoregulatory requirements of fish kept in freshwater, allowing energy normally used in osmoregulation to be used for growth (Gatlin et al, 1992).…”
Section: Introductionmentioning
confidence: 99%